Developments of spray-dried Kombucha tea beverage - Mat Nor, Nor Arifah (2020)
Kombucha tea (KT) is a healthy and refreshing beverage obtained from the fermentation of sugared tea by symbiotic cultures of acetic acid bacteria and fungi. However, KT will eventually turn too sour to drink and will become vinegar if over fermented. Therefore, this study aimed to evaluate the effects of spray drying on the physicochemical, antioxidant and antibacterial properties of KT. Two wall materials including maltodextrin (MD) and Arabic gum (AG) were used. The physiochemical properties of the spray dried kombucha were 16.33±0.58 Brix° for total soluble solid, 3.48±0.13% for moisture content, 0.25±0.34 for water activity, 3.28±0.03 for pH, 0.42±0.004 g/cm3 for bulk density and 47.27±2.50% for wettability. The antibacterial activity significantly (p<0.05) after the kombucha fermentation, while no significant effects observed for the spray drying process on the activity. Spray dried kombucha tea powder produced using AG as wall material showed good physical properties, antioxidant properties and strong antibacterial activity compared to MD. Moreover, second objective is to optimize the condition of production of dried kombucha tea using selected wall materials. Optimization for the spray dried conditions was carried out using surface methodology surface (RSM) with box Behnken design (BBD) for the factors inlet temperature (140 – 180ºC), feed flow rate (25-35 rpm) and aspirator rate (80-100). The optimal conditions estimated for the process were inlet temperature at 178°C, feed flow rate at 25 rpm, and aspirator rate at 80%. The RSM model was significant and inlet temperature was the variable with the greatest impact on most of the responses. The third objective is to characterize the properties of optimized powdered kombucha tea. Metabolomics profiling was performed using ¹H NMR based technique. Major metabolites changes were observed for the significant decline of sucrose (17.8626 mmol/L) in unfermented tea and increase ethanol (1.8393 mmol/L) and glucose (2.6751 mmol/L) in the fresh kombucha tea. The acetic acid was significantly reduced (0.053 mmol/L) and the ethanol was totally degraded in the spray dry kombucha tea. The results indicated that the spray drying process using 10% AG can improve the physiochemical properties of kombucha and sustain it is antioxidant and antibacterial activities. Moreover, the spray drying process caused degradation of ethanol making kombucha safe for alcohol allergic and Halal concerned consumers.